Over and under the wetland - Messner, Kate (Messner, Kate. Over and under., 2024)
Discover the hidden magic of the Everglades in this fascinating and beautiful exploration of the wetland habitat from the New York Times bestselling author and award-winning illustrator of the beloved Over and Under series! Part of the acclaimed nature book series that includes Over and Under the Pond, Over and Under the Rainforest, and Over and Under the Snow, this volume takes readers on a journey into the magical and mysterious reaches of Florida's Everglades National Park. Over the swamp, the barred owl hoots, and the great egret swoops down on snowy wings. The slow mazes of waterways are quiet with the shush of reeds and grasses. But under the swamp's soft shadows, there's a whole hidden world of panthers and orchids, red-bellied turtles and raccoons, lurking alligators and singing frogs. This beautifully illustrated nonfiction picture book reveals all the fascinating creatures living just out of sight in the branches and depths over and under the wetland.